Serpin-independent anticoagulant activity of a fucosylated chondroitin sulfate - Glauser, Bianca F.; Pereira, Mariana S.; Monteiro, Robson Q.; Mourão, Paulo A. S. (Thrombosis and Haemostasis, 2008)
Fucosylated chondroitin sulfate is a glycosaminoglycan from sea cucumber composed of a chondroitin sulfate-like core with branches of sulfated fucose. This glycosaminoglycan has high anticoagulant and antithrombotic activities. Its serpin-dependent anticoagulant activity is mostly due to activating thrombin inhibition by heparin cofactor II. Here, we evaluated the anticoagulant activity of fucosylated chondroitin sulfate using antithrom-bin- and heparin cofactor II-free plasmas. In contrast to mammalian heparin, the invertebrate glycosaminoglycan is still able to prolong coagulation time and delay thrombin and factor Xa generation in serpin-free plasmas. These observations suggest that fucosylated chondroitin sulfate has a serpin-independent anticoagulant effect. We further investigated this effect using purified blood coagulation proteins. Clearly, fucosylated chondroitin sulfate inhibits the intrinsic tenase and prothrombinase complexes, which are critical for thrombin generation. It is possiblethat the invertebrate chondroitin sulfate inhibits interactions between cofactor Va and factor Xa. We also employed chemically modified polysaccharides in order to trace a structure versus activity relationship. Removal of the sulfated fucose branches, but not reduction of the glucuronic acid residues to glucose, abolished its activity. In conclusion, fucosylated chondroitin sulfate has broader effects on the coagulation system than mammalian glycosaminoglycans. In addition to its serpin-dependent inhibition of coagulation protease, it also inhibits the generation of factor Xa and thrombin by the tenase and prothrombinase complexes, respectively. In plasma systems, the serpin-independent anticoagulant effect of fucosylated chondroitin sulfate predominates over its serpin-dependent action. This glycosaminoglycan opens new avenues for the development of antithrombotic agents.
Keywords: Glycosaminoglycan; tenase complex; prothrombinase complex; sea cucumber; heparin